All-Thin-Film Perovskite/C-Si Four-Terminal Tandems: Interlayer and Intermediate Contacts Optimization - Chapa, Manuel (2019)
ALTALUZ (Reference PTDC/CTM-ENE/5125/2014). SuperSolar (PTDC/NAN-OPT/28430/2017). TACIT (PTDC/NAN-OPT/28837/2017). FCT-MEC, Grant SERH/BPD/115566/2016.